Death Penalty For Drugs Dealers and Traffickers From The Perspective of Islamic Law - Jainah, Zainab Ompu; Rachmi Handayani, I Gusti Ayu Ketut (Universitas Islam Negeri Raden Intan Lampung, 2018)
This article examines the Islamic legal perspective on the application of capital punishment against drug dealers/traffickers. The aim is to find out whether these provisions are in accordance with the rules of Islamic law or not. This study uses a normative juridical approach which is carried out by examining legal norms or norms related to the object of discussion. This study finds out that Islamic law does not explicitly regulate drug crime, including determining sanctions for the dealers/traffickers. Islamic law only regulates the crime of liquor (khamer). Therefore, this criminal act can be included in the category of jarîmah ta’zîr which its legal sanctions are left to the authorities policy. Although this crime can be classified as a common crime, it is reasonable that the dealers/traffickers of the illicit goods are given severe punishment, even until sentenced to death, as this crime has a tremendously adverse effect not only for individuals but also for society and the nation as a whole. The sanction is in accordance with the principles of ushûl fiqh.